(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Improving the teacher’s ability to make subject tests is part of the skills that need to be mastered by the teacher in learning. The ability to make subject tests needs to be done as an effort to assess learning activities. Efforts made by the teacher in making subject tests are carried out as a strategy to find out the progress of student learning and to assess their success in teaching students